Social protection in APEC: In pursuit of inclusive growth - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2016)
The paper seeks to take stock of some of the key APEC documents/reports relevant to social protection and safety net programs, and also of the experience of APEC member-economies, with special focus on the Philippines, in implementing social protection measures. In particular, it attempts to identify and analyze social protection issues and challenges within the APEC context. In addition, it aims to provide insights, policy guidelines, and recommendations to improve social protection.
Keywords: 330; social protection; social security; labor market policies; pension; social insurance programs; social assistance; social safety nets